(untitled) (Damascus University Journal of arts and humanities sciences, 2021)
The aim of this research is to study place and all its aspects and dimensions in the poetry of a specific category of the poets of the Umayyad Era, the poetry of the sixth class of the Islamic poets presented by Ibn Sallam Al Jumahee. The poets in this class include Obaid Allah bin Qais Alruqayyat, Al Ahwas, Jameel bin Ma’amar, and Nusaib. Ibn Sallam stated clearly that the link which connects the poets of this class is a place link. According to him, "the sixth class of Islamic poets is Hijazi." He had found out that the mentioned place link is a close connection among the people of one location. On the other hand, he had recognized the effect place has on the poetry of its people. This was perhaps what he wanted to show when he classified some classes according to those who belong to the same place or same environment (the class of Ahl Al Qura, i.e poets of Arab cities). The aim of the research is to reveal how place was manifested in the poetry of the sixth Islamic class on different levels: technical, psychological, and realistic levels. This is done by discussing two types of place: the friendly place, and the unfriendly or the hostile place. The research is also an attempt to find out the common features that characterize the way place is tackled in the poetry of this class of poets. Then the distinctive features of the poetry of each of these poets concerning the way they approach place are described, with explanation of the causes of each poet’s distinction.